Natal Dispersal and Sociality of Young Galapagos Hawks on Santiago Island. - Rivera, Jose Luis.; Vargas, F. Hernan; Parker, Patricia G. (2011)
The Galapagos Hawk (Buteo galapagoensis) is the only diurnal resident raptor in the Galapagos Archipelago,where it exhibits a cooperatively polyandrous mating system. Before breeding, young hawks spend 3-4 years as nonterritorial floaters. Individuals in this age class are highly gregarious on the island of Santiago. Here we examine patterns in natal dispersal and ask whether they appear to develop social affiliations with particular individuals during their juvenile years. Using data collected between 1998 and 2009 from a banded population of 25 territorial groups, we found that natal dispersal is more likely to be to territories adjacent to natal territories than expected by chance, and is not significantly related to the specific type of vegetation of the natal territory. We found no evidence of social affiliations or stable coalitions among particular juveniles; instead they moved in opportunistic aggregations.
English
Keywords: Buteo galapagoensis; Coalitions; Coaliciones; Floater; Flotador; Natal dispersal; Natal dispersión.; Polyandry; Poliandria